Comprehensive energy saving evaluation of circulating cooling water system based on combination weighting method. (5th July 2019) - Zhu, Xiaochen; Niu, Dapeng; Wang, Xu; Wang, Fuli; Jia, Mingxing
Highlights: Various types of evaluation indexes for system energy-saving are analyzed comprehensively. An energy-saving evaluation index system for circulating cooling water system is established. A new method to evaluate the system energy conservation level is proposed. The proposed evaluation method is verified through the practical application. Abstract: The circulating cooling water system is an important industrial auxiliary system and a high energy consumption unit. It is of great practical significance to carry out research on energy conservation of this system. Therefore, this paper establishes a new evaluation index system for comprehensive evaluation of circulating cooling water system through the in-depth analysis of the operating mechanism. This system includes energy consumption index, energy efficiency index, operation quality index and pollution index, and it fulfills a complete energy-saving evaluation of the system in various aspects. Then, in order to balance the subjective experience of experts and the objective information in the data during the evaluation process, this paper designs a combination weighting method based on analytic hierarchy process method and entropy method for carrying out the comprehensive energy saving evaluation. Finally, through the evaluation of an actual network system, the practical application effect of this method is verified, and the comprehensive energy-saving evaluation is realized to the systems which are difficult to evaluate using a single index.